Diachronic Perspectives and Synchronic Variation in Southern Min, 1st edition Chinfa Lien, Alain Peyraube - Lien, Chinfa (Routledge, 2020)
Diachronic Perspectives and Synchronic Variation in Southern Min aims to address a range of grammatical phenomena in Southern Min.